Predicting sleep disordered breathing in outpatients with suspected OSA. Issue 4 (15th April 2014) - Cowan, Douglas C; Allardice, Gwen; MacFarlane, Duncan; Ramsay, Darren; Ambler, Heather; Banham, Stephen; Livingston, Eric; Carlin, Christopher
Abstract : Objective: To validate the utilities of Berlin, STOP and STOP-BANG Questionnaires, other patient characteristics, comorbidities, Epworth Sleepiness Scale (ESS), fractional exhaled nitric oxide (FE NO) and blood markers for the prediction of sleep disordered breathing (SDB) on limited polygraphy. Setting: North Glasgow Sleep Service (a tertiary referral centre). Participants: 129 consecutive patients, aged ≥16 years, referred to the sleep clinic for assessment of possible obstructive sleep apnoea. Interventions: We selected cut-points of apnoea hypopnoea index (AHI) of ≥5 and ≥15/h from their home polygraphy and determined associations of these with individual symptoms, questionnaire scores and other results. Receiver operating characteristic analysis and univariate and multivariate logistic regression were used to explore these. Primary and secondary outcomes measures: Primary : The utility of STOP, STOP-BANG and Berlin Questionnaires for prediction of SDB. Secondary : The utility of other measures for prediction of SDB. Results: AHI was ≥5 in 97 patients and ≥15 in 56 patients. STOP and STOP-BANG scores were associated with both AHI cut-points but results with ESS and Berlin Questionnaire scores were negative. STOP-BANG had a negative predictive value 1.00 (0.77–1.00) for an AHI ≥15 with a score ≥3 predicting AHI ≥5 with sensitivity 0.93 (95% CI 0.84 to 0.98) and accuracy 79%, while a score ≥6 predicted AHI ≥15 with specificity 0.78 (0.65 to 0.88) and accuracy 72%. Neck circumference ≥17 inch and presence of witnessed apnoeas were independent predictors of SDB. Conclusions: STOP and STOP-BANG Questionnaires have utility for the prediction of SDB in the sleep clinic population. Modification of the STOP-BANG Questionnaire merits further study in this and other patient groups.